Individual Characteristics and Their Influence on Organizational Behavior: A Case Study in the Indonesian Public Sector - Jamaluddin Jamaluddin; Muhammad Rif’at Al-Razi (UIN Sunan Gunung Djati, 2025)
This study aims to analyze the contribution of individual characteristics—including capabilities, needs, expectations, and beliefs—to organizational behavior in the public sector, using a case study of the Ministry of Religious Affairs Office in Bandung City, West Java. The urgency of this research rests on the premise that the effectiveness of public organizations is strongly influenced by individual behavior, making the management of employees’ personal characteristics a key factor in improving performance and the quality of public services. This study employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews with leaders and employees of the Ministry of Religious Affairs Office in Bandung City, observations of institutional work dynamics, and a review of official documents. The findings reveal that individual capabilities and experiences strengthen communication, collaboration, and organizational productivity. The fulfillment of physical and spiritual needs enhances employees’ motivation and loyalty, while individual expectations foster achievement orientation and long-term vision. Beliefs serve as the foundation that reinforces communication, collaboration, and a harmonious organizational climate. Overall, individual characteristics directly contribute to shaping organizational behavior that is more adaptive, responsive, and service-oriented. The implications of this study underscore the importance of managerial strategies that strengthen individual characteristics—through continuous capacity building, incentive provision, and the internalization of organizational values—in order to further optimize the quality of public services. The originality of this research lies in its focus on highlighting the micro-level dimension of individual characteristics in shaping organizational behavior in Indonesia’s public sector—a perspective that has been relatively underexplored in prior academic studies.